Research and Implementation of Agreement on a Recording Control - Yanchao Wu; Zhihui Xiao; Yishan Chen (Dianxin kexue)
With the rapid development of wireless high-speed data services，broadband has become an inevitable trend in the development of wireless private network. As one of the private wireless network communication systems，the broadband multimedia cluster system has its own characteristics，which is based on wireless broadband technology，using the form of multimedia services，to command and dispatch functions mainly，etc. During the commanding and dispatching process of the broadband multimedia cluster system，voice，image，video and packet data service become its necessary 1inks and tools. Focusing on how to achieve the broadband multimedia cluster communication system in rea1-time media，and scheduling co11ege storage of information，an audio and video recording contro1 mechanism was researched and designed for efficient storage of multimedia data，through the coordination between switch &contro1 center and record server.